Direct observation of CD4 T cell morphologies and their cross-sectional traction force derivation on quartz nanopillar substrates using focused ion beam technique - Kim, Dong-Joo (Springer, 2013)
Direct observations of the primary mouse CD4 T cell morphologies, e.g., cell adhesion and cell spreading by culturing CD4 T cells in a short period of incubation (e.g., 20 min) on streptavidin-functionalized quartz nanopillar arrays (QNPA) using a high-content scanning electron microscopy method were reported. Furthermore, we first demonstrated cross-sectional cell traction force distribution of surface-bound CD4 T cells on QNPA substrates by culturing the cells on top of the QNPA and further analysis in deflection of underlying QNPA via focused ion beam-assisted technique.